2013
DOI: 10.1128/jvi.03577-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Viral Env Proteins from Acute and Chronic Infections with Subtype C Human Immunodeficiency Virus Type 1 Identifies Differences in Glycosylation and CCR5 Utilization and Suggests a New Strategy for Immunogen Design

Abstract: Understanding human immunodeficiency virus type 1 (HIV-1) transmission is central to developing effective prevention strategies, including a vaccine. We compared phenotypic and genetic variation in HIV-1 env genes from subjects in acute/early infection and subjects with chronic infections in the context of subtype C heterosexual transmission. We found that the transmitted viruses all used CCR5 and required high levels of CD4 to infect target cells, suggesting selection for replication in T cells and not macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
131
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 108 publications
(155 reference statements)
9
131
0
Order By: Relevance
“…In this context, it is critical to know whether transmitted viruses possess unique biological properties that predispose them to establish new infections more efficiently. This is a controversial topic, because some studies have reported TF-specific traits (22,24,26,52,(55)(56)(57), whereas others have failed to confirm these results (27,28,53,58,59). Some of these discrepancies are likely due to the fact that most previous analyses did not compare HIV-1 strains from transmission pairs.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this context, it is critical to know whether transmitted viruses possess unique biological properties that predispose them to establish new infections more efficiently. This is a controversial topic, because some studies have reported TF-specific traits (22,24,26,52,(55)(56)(57), whereas others have failed to confirm these results (27,28,53,58,59). Some of these discrepancies are likely due to the fact that most previous analyses did not compare HIV-1 strains from transmission pairs.…”
Section: Discussionmentioning
confidence: 54%
“…in activated CD4 + T cells but not macrophages (14,(22)(23)(24)(25). Moreover, analysis of a comprehensive panel of infectious molecular clones (IMCs) showed that TF viruses packaged more envelope glycoprotein (Env), exhibited greater infectivity, bound to monocyte-derived dendritic cells more efficiently, and replicated to higher titers in CD4 + T cells in the presence of the type 1 interferon IFNα2 than chronic control (CC) viruses (26).…”
mentioning
confidence: 99%
“…It has been argued that resting T cells may be involved in initial HIV-1 infections at mucosal sites, while infec-tion of activated T cells plays a far greater role during systemic dissemination and propagation of the virus (55). In a recent study, a substantial proportion of chronic viruses (but not transmitted/ founder viruses) were incompletely inhibited by a saturating concentration of MVC (56,57). This viral phenotype was most clearly seen in a cell line expressing very high levels of both CD4 and CCR5, but it was also detectable using primary CD4 ϩ T cells (56).…”
Section: Discussionmentioning
confidence: 99%
“…Most M-tropic variants use the CCR5 coreceptor (R5 M-tropic), but X4 M-tropic viruses have been reported (16). Because M-tropic variants are detected so rarely (3,17), the true frequency and characteristics of M-tropic viruses are only beginning to be explored.…”
mentioning
confidence: 99%
“…The vast majority of HIV-1 isolates sampled during acute and chronic infections are CCR5-using T cell-tropic (R5 T-tropic) viruses, which are adapted to (1)(2)(3), and replicating in (4-6), CD4 ϩ memory T cells. R5 T-tropic viruses require the high densities of the CD4 receptor found on CD4 ϩ T cells for efficient entry and use the CCR5 coreceptor, which is most abundant on the memory subset of CD4 ϩ T cells.…”
mentioning
confidence: 99%